Autonomous Indoor Customization: The Future of Human Comfort and Productivity - Akintola, Adeyinka; Ma, Jun; Hossein Motlagh, Naser; Bouloukakis, Georgios; Flores, Huber (Computer : a publication of the IEEE Computer Society, 2025)
Humans spend most of their time indoors, engaged in work, recreation, and leisure activities. Indoor spaces are in constant flux due to these dynamic activities, making comfort a persistent challenge. Current IoT and pervasive technologies have made strides in addressing this issue, but the growing autonomy of these systems presents new opportunities for customizing indoor spaces. Advanced service robots, autonomous indoor drones, and a broad spectrum of indoor sensing technologies can work together to enhance the quality of indoor living. In this paper, we present a research vision for autonomous customization of indoor spaces using autonomous technologies. By examining the current maturity of these technologies and existing enablers, we outline our vision and highlight how they can drive innovative scenarios. In the light of our result, we present a research agenda that identifies key technical challenges and the opportunities associated with this emerging field. Our work sets the foundation for transforming indoor spaces through proactive interactions initiated by autonomous and intelligent devices.